2021
DOI: 10.1002/rnc.5488
|View full text |Cite
|
Sign up to set email alerts
|

Exact computation of maximal allowable delay for general second‐order multi‐agents consensus

Abstract: The delay consensus margin (DCM) defines the largest delay range within which a distributed feedback control protocol can achieve and maintain the consensus robustly against uncertain time delays. This article investigates the exact computation of the DCM for general second-order multi-agent systems (MASs) under distributed proportional-derivative (PD) feedback, or alternatively known as position and velocity feedback protocols over undirected graphs. We consider MASs with uncertain constant delays, and derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Second‐order agents are highly pertinent to the modeling of mechanical systems such as interconnected Lagragian manipulators 21 and interconnected vehicles, 48 where the position and velocity are the states of the system, and to the modeling of electrical systems such as a microgrid, 49,50 where the phase and frequency are the states. It is worth noting that with state‐feedback protocols, the DCM problem was examined in Reference 51 for second‐order systems, where the DCM is also cast as a quasi‐concave optimization problem. It is possible to extend the approach of Reference 51 to output feedback control of nonminimum phase agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second‐order agents are highly pertinent to the modeling of mechanical systems such as interconnected Lagragian manipulators 21 and interconnected vehicles, 48 where the position and velocity are the states of the system, and to the modeling of electrical systems such as a microgrid, 49,50 where the phase and frequency are the states. It is worth noting that with state‐feedback protocols, the DCM problem was examined in Reference 51 for second‐order systems, where the DCM is also cast as a quasi‐concave optimization problem. It is possible to extend the approach of Reference 51 to output feedback control of nonminimum phase agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that with state‐feedback protocols, the DCM problem was examined in Reference 51 for second‐order systems, where the DCM is also cast as a quasi‐concave optimization problem. It is possible to extend the approach of Reference 51 to output feedback control of nonminimum phase agents. Likewise, in such extensions, it is of interest to explore how zero and pole characteristics may confine the consensus performance, and more generally how higher‐order dynamic feedback protocols may mitigate the adversary agent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Proposition 1. Consider the MAS (1) in the presence of actuator attacks (9) and sensors attacks (10). Under the standard consensus protocol (4), the normal followers that have access to an attacked follower through directed paths are unable to achieve state consensus with the leader.…”
Section: Analysis Of Impacts Of Attacks On Standard Consensus Protocolmentioning
confidence: 99%
“…With technical progress in sensing, communication and control domains, multi‐agent systems (MASs) have attracted an increasing number of attention from researchers 1‐5 . MASs have widespread applications in several areas, such as robot teams, 6 sensor networks, 7 and satellite clusters 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 17 investigated consensus robustness with respect to variable network delays, where robustness is measured by the delay consensus margin (DCM), that is, the largest range of delay allowable to ensure consensus attainment in spite of variations in the delay. They considered second‐order multi‐agent systems under distributed PD feedback, alternatively known as position and velocity feedback protocols, and showed that the exact delay consensus margin can be obtained by solving a univariate quasi‐concave optimization problem.…”
Section: Overview Of Articlesmentioning
confidence: 99%